Leaving Performance-Oriented Goal (Ranking) Based Education To Improve Student Learning Motivation - Rai Saba, Mahitri Wiyani; Sutarti, Titin (International Journal of Multidisciplinary Sciences, 2024)
Society believes that ranking can be extrinsic motivation for students to improve learning performance, achievement, and student achievement. Ranking also makes it easier for schools to find out the quality of schools, formulate policies, and select colleges to enter. On the other hand, ranking triggers "competition" not only among students, but also between parents. The pressure that children feel to always "achieve" in this case to win in class, is also getting higher. However, reflecting on the quality of Indonesian education, the rankings did not function as expected. This can be seen from the results of the 2018 PISA test which showed Indonesia was ranked 72nd out of 77 countries. The research aims to understand the purpose and effectiveness of the learning process based on performance-oriented goals in education and to find alternative learning methods that are more effective in motivating students through learning process orientation. The method used in this research is library research, namely research carried out by reading, studying and recording various literature or reading materials that are appropriate to the subject matter. The results of the study explain that basically ranking is no longer relevant for use in schools because it will encourage performance-oriented goals in students. This condition is exacerbated by the infrastructure, facilities, and number of teaching staff that are not in line with the existing learning demands. There is a need for a system change that is more oriented towards learning-oriented goals to maximize the learning process and revive students' interest in learning.